Postnatal Development of the Amygdala: A Stereological Study in Macaque Monkeys - Chareyron, Loïc J. (2012)
Abnormal development of the amygdala has been linked to several neurodevelopmental disorders, including schizophrenia and autism. However, the postnatal development of the amygdala is not easily explored at the cellular level in humans. Here we performed a stereological analysis of the macaque monkey amygdala in order to characterize the cellular changes underlying its normal structural development in primates. The lateral, basal, and accessory basal nuclei exhibited the same developmental pattern, with a large increase in volume between birth and 3 months of age, followed by slower growth continuing beyond 1 year of age. In contrast, the medial nucleus was near adult size at birth. At birth, the volume of the central nucleus was half of the adult value; this nucleus exhibited significant growth even after 1 year of age. Neither neuronal soma size, nor neuron or astrocyte numbers changed during postnatal development. In contrast, oligodendrocyte numbers increased substantially, in parallel with an increase in amygdala volume, after 3 months of age. At birth, the paralaminar nucleus contained a large pool of immature neurons that gradually developed into mature neurons, leading to a late increase in the volume of this nucleus. Our findings revealed that distinct amygdala nuclei exhibit different developmental profiles and that the amygdala is not fully mature for some time postnatally. We identified different periods during which pathogenic factors might lead to the abnormal development of distinct amygdala circuits, which may contribute to different human neurodevelopmental disorders associated with alterations of amygdala structure and functions.